Daya terima konsumen terhadap jelly drink belimbing wuluh - Romadhiyana Kisno Saputri; Akhmad Al-Bari; Ria Indah Kusuma Pitaloka (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Belimbing wuluh (Averrhoa bilimbi L.) is a well-known traditional medicinal plant that thrives in Indonesia. The amount of fruit production per year can reach 1500 pieces per plant but is easily damaged, its shelf life is short, the taste of sour fruit causes not many people to consume the fruit fresh, in addition, have a low selling price and economic value. Therefore to increase the storage capacity, selling price, and economic value it is necessary to process into functional foods such as jelly drinks. This study aims to determine consumer acceptance of Belimbing wuluh (Averrhoa bilimbi L.) jelly drink products. The method of this research was the design of random group. The first factor is the concentrate of carrageenans (1%; 1,5%; 2%) and the second factor is the concentrate of sugars (13%, 15%). Observations on Belimbing wuluh (Averrhoa bilimbi L.) jelly drink (taste, color, aroma, suction power, and mouthfeel) by 25 untrained panelists. Organoleptic test data were analyzed by nonparametric statistical methods using the Friedman test. The results showed that the best treatments on consumer acceptance of jelly drink Belimbing wuluh (Averrhoa bilimbi L.) in an organoleptic manner was obtained from treatment with 1,5% carrageenan and 15% sugar with a product value of 2,39 with a mean value of panelist favorability to taste on 6,23; the color on 7,76; aroma on 7,19; suction power on 8,5; mouthfeel on 7,54.